2022
DOI: 10.1002/oby.23562
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time‐restricted eating on sex hormone levels in premenopausal and postmenopausal females

Abstract: Objective: Concerns have been raised regarding the impact of time-restricted eating (TRE) on sex hormones in females. This study examined how TRE affects sex steroids in premenopausal and postmenopausal females.Methods: This is a secondary analysis of an 8-week TRE study (4-to 6-hour eating window) conducted in adults with obesity. Men and perimenopausal females were excluded. Females were classified into two groups based on menstrual status: premenopausal (n = 12) or postmenopausal (n = 11).Results: After 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In premenopausal women undergoing time‐restricted eating (4‐ to 6‐h eating window during 8 weeks), a recent study showed that body weight decreased with decreasing dehydroepiandrosterone concentrations. These changes were not associated with significant changes in circulating levels of testosterone, androstenedione and sex hormone binding globulin 31 . A recent review focusing on the effects of intermittent fasting on reproductive hormone levels reported the lack of significant effects of fasting on oestrogen, gonadotropins or prolactin levels in women 32 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In premenopausal women undergoing time‐restricted eating (4‐ to 6‐h eating window during 8 weeks), a recent study showed that body weight decreased with decreasing dehydroepiandrosterone concentrations. These changes were not associated with significant changes in circulating levels of testosterone, androstenedione and sex hormone binding globulin 31 . A recent review focusing on the effects of intermittent fasting on reproductive hormone levels reported the lack of significant effects of fasting on oestrogen, gonadotropins or prolactin levels in women 32 .…”
Section: Discussionmentioning
confidence: 92%
“…These changes were not associated with significant changes in circulating levels of testosterone, androstenedione and sex hormone binding globulin. 31 A recent review focusing on the effects of intermittent fasting on reproductive hormone levels reported the lack of significant effects of fasting on oestrogen, gonadotropins or prolactin levels in women. 32 Further studies must address the potential relationships between intermittent fasting, body fat distribution and sex hormones in healthy and unhealthy women.…”
Section: Effect On Body Weightmentioning
confidence: 99%
“…As for postmenopausal females, TRE had no effect on estradiol, estrone, progesterone, testosterone, androstenedione, and SHBG concentrations, as documented in the Kalam study. 3 Taken together, TRE may decrease testosterone in males and premenopausal females, but does not appear to alter sex steroids in postmenopausal females.…”
Section: Discussionmentioning
confidence: 98%
“…6 In females, changes in sex hormones have only been examined in two TRE trials. 3, 4 In premenopausal females, reductions in total testosterone accompanied by increases in SHBG levels have been observed after 1 month of 8-h TRE in the trial by Li et al 4 In contrast, Kalam et al 3 reported no changes in total testosterone and SHBG levels after 2 months of TRE with shorter eating windows (4-6 h) in premenopausal females. As for postmenopausal females, TRE had no effect on estradiol, estrone, progesterone, testosterone, androstenedione, and SHBG concentrations, as documented in the Kalam study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation